1990
DOI: 10.1017/s0950268800047725
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a pseudo-outbreak of ‘Pseudomonas thomasii’ in a special-care baby unit by numerical analysis of SDS–PAGE protein patterns

Abstract: Forty-two cultures of pseudomonas comprising 28 clinical isolates from a pseudo-outbreak on a Special-Care Baby Unit and 14 reference strains, including 9 type strains, of various Pseudomonas species, were characterized by one-dimensional sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) of whole-cell proteins. The protein patterns were highly reproducible and were used as the basis for a numerical analysis which divided the strains into 9 phenons. Two of the 28 clinical isolates were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Although the study of King et al (1979) was not conclusive and failed to establish ' P. thomasii ' as a valid species, Costas et al (1990) concluded that SDS-PAGE of whole-cell proteins provided clear evidence that R. pickettii and ' P. thomasii ' were separate taxa, a finding confirmed by this study. On the other hand, Pan et al (1992) reported that HPLC analysis of cell wall fatty acids could not distinguish R. pickettii biovar Va-1 from R. pickettii biovar 3\' thomasii ', findings also confirmed by this study.…”
Section: Differentiation Of R Mannitolytica At the Species And Genussupporting
confidence: 52%
See 2 more Smart Citations
“…Although the study of King et al (1979) was not conclusive and failed to establish ' P. thomasii ' as a valid species, Costas et al (1990) concluded that SDS-PAGE of whole-cell proteins provided clear evidence that R. pickettii and ' P. thomasii ' were separate taxa, a finding confirmed by this study. On the other hand, Pan et al (1992) reported that HPLC analysis of cell wall fatty acids could not distinguish R. pickettii biovar Va-1 from R. pickettii biovar 3\' thomasii ', findings also confirmed by this study.…”
Section: Differentiation Of R Mannitolytica At the Species And Genussupporting
confidence: 52%
“…Retrospectively, a strain stored previously as P. fluorescens and isolated repeatedly from an abdominal haematoma of a patient with cholangiocarcinoma and a strain from an outbreak due to contaminated water in the neonatal intensive care department of the Ghent University Hospital, Belgium (GUH), in 1990 could also be identified as R. mannitolytica. Several nosocomial outbreaks with R. pickettii biovar 3\' thomasii ', mostly due to contaminated fluids, have been described (Costas et al, 1990 ;Pan et al, 1992 ;Phillips et al, 1972), but no life-threatening infections have been reported yet to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…thomasii." A pseudo-outbreak has been described as well (4). Although no serious non-outbreak-related infections have been described thus far, the clinical importance of R. mannitolilytica may have been overlooked, possibly due to misidentification as P. fluorescens, B. multivorans, and/or R. pickettii.…”
Section: Reduction Of Nitratementioning
confidence: 99%
“…Environmental contamination of medical and laboratory equipment resulting in outbreaks and pseudo-outbreaks is often due to multiple species/strains of microorganisms (12,13). This is in contrast to the situation in outbreaks and pseudo-outbreaks due to point sources, where a single strain of microbe is often involved (14).…”
mentioning
confidence: 99%